Natural gas as an energy alternative of land transport to reduce the emission of carbon dioxide. - Romero-Cóndor, Lucio L. (2019)
The object of the investigation is to reduce the emission of carbon dioxide (CO ) from the internal combustion engine of the car park of the Huánuco region, for this purpose it was analyzed by type of fuel consumed by terrestrial transport using the methodology of stoichiometry, Quantifying the emission of CO in l / day, and also analyzed the use of natural gas as an energy alternative for land transportation with the same methodology, observing a high feasibility of replacing liquid fuels with environmentally friendly, Mainly by methane and that can be produced by sustainable processes, above all that Peru possesses important proven reserves of natural gas. The study estimates the environmental and economic benefit in four scenarios; The use of natural gas as energy for the internal combustion engine generates a significant reduction of 182.64 t / day of carbon dioxide (CO ) in the land transport of Huánuco in relation to the current consumption of liquid fuel, the low cost in The national market for this energy reduces; The cost of operating the vehicle, provides higher compression ratio, higher octane rating, higher calorific value, efficiency and safety in the combustion of the engine. This energy change promotes the conversion of the engine, start-up of transport projects with clean energies, optimization of the operation of the engines and the reformulation of the usual fuels.